Informing about childbirth without increasing anxiety: a qualitative study of first-time pregnant women and partners' perceptions and needs - Anne-Sylvie Diezi; Mélanie Vanetti; Marie Robert; Béatrice Schaad; David Baud; Antje Horsch (BMC, 2023)
Abstract Background Complications requiring medical interventions during childbirth are far from rare, even after uncomplicated pregnancies. It is often a challenge for maternity healthcare professionals to know how to prepare future parents for these eventualities without causing unnecessary anxiety. Studies on traumatic birth experiences have shown that feelings of loss of control, insufficient information, and lack of participation in medical decisions during childbirth are factors of difficult experiences. However, little is known about the information and communication needs of expectant parents about childbirth during the prenatal period. To gain a deeper understanding of the information and communication needs of first-time pregnant women and partners, we explored their perceptions and expectations for their upcoming childbirth, and the actions they initiated to prepare for it. Methods Semi-structured interviews were conducted individually with first-time pregnant women and partners of pregnant women aged 18 years or older, with an uncomplicated pregnancy. Thematic analysis was used to identify themes and sub-themes. Results Twenty expectant parents (15 pregnant women and five partners of pregnant women) were interviewed. Six themes were identified: Childbirth event; Childbirth experience; Childbirth environment; Organisation of care; Participation in decision making; Roles within the couple and transition to parenthood. Conclusions This study contributes to a better understanding of the information needs of future parents expecting their first child. Results highlighted that the notion of "childbirth risks" went beyond the prospect of complications during birth, but also encompassed concerns related to a feeling of loss of control over the event. Expectant parents showed an ambivalent attitude towards consulting risk information, believing it important to prepare for the unpredictability of childbirth, while avoiding information they considered too worrying. They expressed a desire to receive concrete, practical information, and needed to familiarise themselves in advance with the birth environment. Establishing a respectful relationship with the healthcare teams was also considered important. The findings suggest that information on childbirth should not be limited to the transmission of knowledge, but should primarily be based on the establishment of a relationship of trust with healthcare professionals, taking into account each person's individual values and expectations.